2009
DOI: 10.1007/s00296-009-1209-8
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus as a first presentation of common variable immunodeficiency associated with infrequent mannose-binding lectin gene polymorphisms

Abstract: The association of common variable immunodeficiency (CVID) and Systemic Lupus Erythematosus (SLE) is infrequent. Mannose-binding lectin (MBL) has been shown to play a role in CVID and SLE. The purpose of this study is to describe two cases of CVID who presented as SLE and also evaluate the presence of MBL polymorphisms and MBL serum levels in those patients.In both patients, SLE was the first manifestation of CVID. In these patients the SLE immunological markers and disease activity disappeared after the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…Takahashi et al [14] did not evidence any association between MBL2 alleles and disease characteristics, (only patients homozygous for the B allele tended to have a higher risk of infection during treatment), whereas other studies associated MBL2 allelic variants with a particular SLE clinical manifestation, i.e., arterial thrombosis [19], cardiovascular diseases [20], or common variable immunodeficiency (CVID) [21]. Jakab et al [22] found that homozygotes for MBL2 promoter X allele were significantly younger at diagnosis and also had significantly higher risk of development of cutaneous manifestations and pleuritis/pericarditis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Takahashi et al [14] did not evidence any association between MBL2 alleles and disease characteristics, (only patients homozygous for the B allele tended to have a higher risk of infection during treatment), whereas other studies associated MBL2 allelic variants with a particular SLE clinical manifestation, i.e., arterial thrombosis [19], cardiovascular diseases [20], or common variable immunodeficiency (CVID) [21]. Jakab et al [22] found that homozygotes for MBL2 promoter X allele were significantly younger at diagnosis and also had significantly higher risk of development of cutaneous manifestations and pleuritis/pericarditis.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have investigated and in some case also disclosed a possible association between MBL, MBL2 polymorphisms, and SLE development as well as clinical features; controversial results have sometimes been obtained [11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Two patients who developed CVID after SLE also carried the very infrequent Mannose-binding lectin (MBL) haplotype 4Q-57Glu. One of them, who had low levels of circulating MBL, presented a severe phenotype with frequent lower respiratory tract infections and development of bronchiectasis, thus suggesting that the coexistence of alterations of the innate and acquired immune system could be associated with a greater susceptibility to infectious and autoimmune diseases (59).…”
Section: Infections Inflammation and Autoimmunity In Cvidmentioning
confidence: 99%
“…The fact that lupus-prone mice that lack soluble antibodies still develop lupus-like disease supports the idea that SLE pathology may occur independently of soluble autoantibodies [58]. Indeed, instead of hypergammaglobulinemia, decreased immunoglobulin levels or even typical combined variable immunodeficiency (CVID) [59, 60] is seen in some SLE patients. As many as 6% of SLE patients display concurrent IgA deficiency and the same drugs that have been associated with this, have also been associated to the development of SLE (e.g.…”
Section: Defective Immune Response and Pathogen Clearance In Slementioning
confidence: 95%